From the Conference Chair of The Learning Ideas Conference 2021 - Guralnick, David (International Journal of Advanced Corporate Learning (iJAC), 2022)
A note from the conference chair of The Learning Ideas Conference 2021, introducing a special issue of iJAC focused on papers related to presentations from the conference.